2008
DOI: 10.1590/s0100-69162008000100012
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de lisímetro de pesagem hidráulica de baixo custo no semi-árido nordestino

Abstract: RESUMO:Medidas diretas de evapotranspiração de referência são importantes na avaliação e na calibração de métodos indiretos. Avaliou-se o desempenho de lisímetro de pesagem hidráulica de baixo custo, visando à determinação direta da evapotranspiração de referência (ETo), em área de assentamento rural no Semi-Árido nordestino. O lisímetro é de concepção simplificada, com travesseiros hidráulicos confeccionados com mangueira flexível de butil e revestida em náilon, interligados a um sistema manométrico com mercú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
(8 reference statements)
0
1
1
7
Order By: Relevance
“…Compared to other studies, hydraulic weighing lysimeters constructed by Santos et al (2008), showed mean errors of up to 3.93 and 1.73%, respectively, using mercury manometer. It is noteworthy that Black et al (1968), quoted by Silva et al (2003), stated that the tolerable error limit is 10%, as tank inclination influences fluid deformity in hydraulic cells, causing lysimeter reading errors.…”
Section: Calibration and Stability Coefficientcontrasting
confidence: 54%
“…Compared to other studies, hydraulic weighing lysimeters constructed by Santos et al (2008), showed mean errors of up to 3.93 and 1.73%, respectively, using mercury manometer. It is noteworthy that Black et al (1968), quoted by Silva et al (2003), stated that the tolerable error limit is 10%, as tank inclination influences fluid deformity in hydraulic cells, causing lysimeter reading errors.…”
Section: Calibration and Stability Coefficientcontrasting
confidence: 54%
“…Crop transpiration and water evaporation from the soil constitute the process of evapotranspiration, which can be estimated through different methods or determined under local conditions, through lysimeters; the latter is the most indicated, because of the intrinsic characteristics of each site, such as climate, vegetation and relief (Mendonça et al, 2003;Faria et al, 2006;Santos et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Constatou-se excelente linearidade com as massas adicionadas em cada lisímetro e o sinal obtido da célula de carga com histerese mínima. Santos et al (2008) No ensaio foram observados valores de sensibilidade a partir de 1 kg correspondendo a uma variação de 0,0033mV ou 3,33µV (microvolts) ou 0,370 mm. Os valores observados estão condizentes com o desejado, pois mesmo que a resolução do datalogger possibilite a sensibilidade a partir de 0,100g o mesmo foi configurado para detectar variação acima de 1 Kg.…”
Section: Calibraçãounclassified